2015
DOI: 10.1111/dme.12787
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle‐related risk factors and trajectories of work disability over 5 years in employees with diabetes: findings from two prospective cohort studies

Abstract: AimsTo examine work disability trajectories among employees with and without diabetes and identify lifestyle‐related factors associated with these trajectories.MethodsWe assessed work disability using records of sickness absence and disability pension among participants with diabetes and age‐ sex‐, socio‐economic status‐ and marital status‐matched controls in the Finnish Public Sector Study (1102 cases; 2204 controls) and the French GAZEL study (500 cases; 1000 controls), followed up for 5 years. Obesity, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…We found that a large proportion of the individuals either showed stable high levels (30.4%) or increasing number (16.1%) of annual SA/DP months preceding suicide. This is in contrast to much lower levels or lower proportions of high/increasing work disability in individuals prior to multiple sclerosis and first diagnosis of diabetes in recent studies based on a Swedish cohort (<23%) [ 29 ], and a Finnish (<29%) and a French (<13%) occupational cohort [ 16 ]. High levels of SA/DP seem to be associated with the type and severity of the underlying diagnoses of SA/DP [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We found that a large proportion of the individuals either showed stable high levels (30.4%) or increasing number (16.1%) of annual SA/DP months preceding suicide. This is in contrast to much lower levels or lower proportions of high/increasing work disability in individuals prior to multiple sclerosis and first diagnosis of diabetes in recent studies based on a Swedish cohort (<23%) [ 29 ], and a Finnish (<29%) and a French (<13%) occupational cohort [ 16 ]. High levels of SA/DP seem to be associated with the type and severity of the underlying diagnoses of SA/DP [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 76%
“…Work-related functional impairment has been demonstrated to have different trajectories before diagnosing of chronic diseases, e.g. diabetes [ 16 ]. Knowledge on work-related trajectories may be beneficial for early identifying patients at higher risk.…”
Section: Introductionmentioning
confidence: 99%
“…The current study is relatively novel in its application of the GBTA method. A French-Finnish study analysed work disability trajectories using the annual number of work disability days, not months, as a repeated end-point among employees with and without diabetes (Virtanen et al, 2015). Despite the differences in the study designs and the length of the follow-up periods, some similarities are evident.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the association between mental ill-health and work disability by focusing on either frequential (SA) or dichotomous (DR) end-points (Ahola et al, 2011;Knudsen et al, 2013;Lahelma et al, 2015;Mauramo et al, 2018) but less research has considered heterogeneity in the development of work disabilities over time using a trajectory modelling approach (Farrants et al, 2018;Feldt et al, 2009;Laaksonen et al, 2016;Virtanen et al, 2015). A study analysing disability benefit records of all Finnish residents aged 30 to 64 found that DR awards follow heterogeneous SA trajectories, and that these trajectories were associated with the diagnostic reason of the DR award (Laaksonen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation